DESAIN APLIKASI WEB UNTUK MENGELOLA DATA MAGANG DI FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS TARUMANAGARA - Maria Rosa Gosal; Wasino; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Universitas Tarumanagara, particularly the Faculty of Information Technology, supports the Merdeka Belajar-Kampus Merdeka (MBKM) industrial internship program to enhance student competencies through partnerships with companies and the provision of accessible information on internship vacancies. However, the current system used for managing these internships faces limitations that impact the effectiveness of industrial internship management. Many processes remain manual, leading to inefficiencies, delays, and an increased risk of data errors, which complicate comprehensive monitoring of student internship activities by both the university and partner companies. To address these issues, a web application is designed to eliminate these limitations and automate manual tasks. This solution aims to enhance the efficiency of internship data management, reduce recording errors, and enable real-time monitoring of internship activities, fostering transparency and accountability. The application design employs the Software Development Life Cycle (SDLC) methodology, specifically the structured and sequential waterfall model. This approach systematically defines requirements from the beginning and ensures that each development stage is completed before progressing to the next. The waterfall model is chosen for its clarity and orderly progression, ensuring that the application effectively meets the needs of all users, including students, faculty supervisors, company mentors, and administrators.